2021
DOI: 10.1111/ijcp.14067
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of postoperative ischemic stroke after coronary artery bypass grafting

Abstract: Although coronary artery bypass grafting (CABG) has been shown to be safe and effective in appropriately selected patients, 1,2 ischemic stroke is a potentially devastating complication that is associated with increased risk of both short-and long-term morbidity and mortality. 3,4 The most common mechanism of stroke following CABG is related to emboli originating from the ascending aorta during cross-clamping, cannulation, and creation of proximal anastomoses; however, intracardiac thrombi, hypoperfusion, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…Contrary to existing literature, 3,4 this study did not show peripheral vascular disease (PVD) as a significant risk factor for postoperative CVA. The authors contributed this to the definition of PVD within VASIP which included patients who have previously undergone peripheral revascularization.…”
contrasting
confidence: 99%
“…Contrary to existing literature, 3,4 this study did not show peripheral vascular disease (PVD) as a significant risk factor for postoperative CVA. The authors contributed this to the definition of PVD within VASIP which included patients who have previously undergone peripheral revascularization.…”
contrasting
confidence: 99%
“…42 Risk factors of postoperative stroke include advanced age, diabetes mellitus, cerebrovascular disease, atherosclerotic disease, and perioperative AF. 43 , 44 A study conducted by Wang et al 21 indicated that patients who developed new-onset AF had an increased risk of postoperative stroke (OR, 1.53; 95% CI, 1.08-2.18; P = .017) and higher mortality (HR, 1.49; 95% CI, 1.22-1.81; P < .001) compared with patients without AF after cardiac surgery. 21 The key question is: if we were able to reduce the incidence of POAF through DEX use, would we then lower the incidence of postoperative stroke?…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative stroke is one of the most feared complications after cardiac surgery and is associated with increased mortality, prolonged hospital stay, and higher total hospitalization costs 1–3 . Age (>60 years), dialysis dependency, chronic lung disease, atrial fibrillation, and vessel disease represents the most common preoperative risk factors for stroke 3 .…”
mentioning
confidence: 99%
“…Postoperative stroke is one of the most feared complications after cardiac surgery and is associated with increased mortality, prolonged hospital stay, and higher total hospitalization costs 1–3 . Age (>60 years), dialysis dependency, chronic lung disease, atrial fibrillation, and vessel disease represents the most common preoperative risk factors for stroke 3 . In addition, plenty of intraoperative risk factors may be associated with a higher risk of postoperative stroke: atherosclerosis or calcification of the aorta, aortic manipulation during coronary bypass surgery, and conventional on‐pump coronary artery bypass grafting (CABG), and prolonged time on cardiopulmonary bypass 1,4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation